Affecting Financial Inclusion Toward Third Deposit Funds of Islamic Banking Indonesia - Muhammad Khozin Ahyar; Abdul Hakim (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This study aims to determine the effect of financial inclusion variables on third-party deposit funds used in Islamic banking. In general, this study uses financial inclusion and non-financial inclusion variables. Financial inclusion variables are proxied by office networks, ATM networks, and savings customers. Financial inclusion variables are proxied by office networks, ATM networks, and savings customers. Third deposit funds, interest rates, profitability, yield equivalent, and the size of sharia banking are all used as non-financial inclusion variable proxies. This quantitative study used the Vector Error Correction Model (VECM) and the Eviews analysis tool. The cointegration test probability value (0.0228 < 0.05) indicates that the data used in the study are cointegrated. According to the data analysis, the office network (2,60397) and the ATM network (2.48865) serve as proxies for financial inclusion variables affecting Islamic banking deposits. The deposit customer (1,55953), on the other hand, is a proxy variable that has no effect. The equivalent yield (2,48469) and Islamic banking size (2,77972) are non-financial inclusion variables influencing Islamic banking deposits. The benchmark interest rate (-0,29262) and profitability (0,90000), on the other hand, do not affect Islamic banking deposits.